Fiji Sugar Corporation: a legitimacy theory perspective - Mohammed Riaz Azam; Ruvendra Kumar Nandan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of the study is to identify the strategies that Fiji Sugar Corporation Limited (FSC) has applied to receive Fiji Government’s ongoing financial support despite making continuous substantial losses over the years. Using a theoretical framework informed by legitimacy theory, the authors predict the strategies used by FSC. The study applied qualitative document analysis method and examined archival data such as scholarly articles, newspaper articles, and annual reports’ data for the periods covering from 2014 to 2018. The means of triangulation was challenging as interviews with the relevant participants were not possible due to Covid-19 pandemic and lockdowns. The findings of the study highlight that FSC has strategically utilized its existence and continuation to emphasize the economic and social dislocation its closure will create to the people of Fiji who depend on the sugar industry for their livelihood. This strategy has enabled FSC to receive Government’s continued support together with the unachievable promises that FSC is making all these years which is to improve its financial performances. The findings also suggest that FSC has smartly accepted its operational failures but has manipulated the cause of the failures beyond its control. The study contributes to the academic discussion on the strategies that an organization can adopt to maintain its legitimacy and continuation.